Error Analysis of Sundanese English Pronunciation on Fricatives Sound - Fakhri Fauzi (Buletin Al-Turas, 2014)
AbstraksPenelitian ini bertujuan untuk mengetahui kesalahan-kesalahan umum yang biasanya ditemukan pada mahasiswa suku Sunda yang ada di jurusan Bahasa dan Sastra Inggris tahun ajaran 2013 dalam mengikuti matakuliah pronounciation, khususnya pada masalah bunyi mendesis. Adapun fokus penelitian ini ditujukan pada mahasiswa baru yang berlatarbelakang budaya Sunda dengan tujuan untuk mengetahui keakurasian pengucapan kata-kata yang mengandung unsur desisan/desahan. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Peneliti sebagai pengumpul data melakukan hal-hal sebagai berikut: melalui observasi langsung terhadap mahasiswa suku Sunda. Merekam atau mencatat cara pengucapan (pronounciation) dan menganalisis kesalahan-kesalahannya berdasrkan konsep Error Analisis dari beberapa sumber. Hasil penelitian ini menyimpulkan bahwa mahasiswa yang berasal dari Sunda pada umumnya bnyak melakukan kesalahan dalam pengucapan kata-kata yang mengandung desahan. Dengan demikian hasil penelitian ini diharapkan dapat memberikan koreksi dan masukan bagi para pelajar atau mahasiswa yang berasal dari Sunda.---AbstractThis study is aimed to find out the errors that commonly made by Sundanese student of English Letters Department in the year 2013 who already taken a pronunciation class, in pronouncing a fricative sounds. The reseacher focuses on freshman student who has Sundanese cultural background to know their accuracy in pronouncing some fricative’s words. The reseacher uses qualitative method on writing his thesis. He also analyzes the collected data through descriptive analysis technique in order to reach the objective of the research. The reseacher involves himself to collect data by observing the respondents, recording their pronunciation and analyzing the error on their pronunciation based on theories of error analysis which are taken from some relevant references. On the conclusion, the reseacher finds that Sundanese student of English Letters Department are made some error on their pronunciation. Error of omission and error of addition are found on the vowels and consonant sound except the fricatives sound. While error of selection, is occurred both on the fricatives sound and the rest of sound. The reseacher also finds that overgeneralization is one of the reasons why the Sundanese student made errors on their pronunciation.